2014
DOI: 10.2320/matertrans.m2013352
|View full text |Cite
|
Sign up to set email alerts
|

Alloy Designs of High-Entropy Crystalline and Bulk Glassy Alloys by Evaluating Mixing Enthalpy and Delta Parameter for Quinary to Decimal Equi-Atomic Alloys

Abstract: The values of mixing enthalpy (¦H mix ) and Delta parameter (¤) were calculated with 73 elements from Miedema's model for multicomponent equi-atomic alloys to investigate the possibilities of the alloys to be formed into high-entropy (H-E) alloys or high-entropy bulk metallic glasses (HE-BMGs). The equi-atomic alloys from about 15 million ( 73 C 5 ) quinary to 621 billion ( 73 C 10 ) decimal systems were evaluated by referring to a ¦H mix ¤ diagram for zones S and B's for H-E alloys with disordered solid solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Fig.3Relationship between the VEC and phase(s) of the HEAs prepared in this study and reported M/HEAs 14,…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Fig.3Relationship between the VEC and phase(s) of the HEAs prepared in this study and reported M/HEAs 14,…”
mentioning
confidence: 81%
“…13), which are now widely used to describe those of elements in HEAs. Takeuchi et al 14) presented candidates for face-centered cubic (FCC) HEAs by evaluating mixing enthalpy and ¤. Guo and co-workers proposed that the valence electron concentration (VEC) is the most promising parameter that dictates the formation feasibility of FCC, body-centered cubic (BCC), and FCC+BCC phases.…”
Section: Introductionmentioning
confidence: 99%
“…More speci cally, the zone S in a trapezoid shape for disordered HEAs in the δ-ΔH mix diagram is de ned 21) by eqs. (1) and (2), which were also referred to in the authors previous study 22) .…”
Section: Resultsmentioning
confidence: 93%
“…Recently, so-called high-entropy metallic glasses attracted the attention of materials science researchers. [1][2][3][4][5] Since the quinary and higher-order systems have a very large temperature and composition space, most of which remains experimentally unexplored, methods for rapid screening of promising combinations of elements and compositions have become an important topic in scientific discussion. As a rule, such methods are based on the analysis of the thermodynamic and physical parameters, such as mixing enthalpy, configurational and mismatch entropies, valence electron concentration, and others.…”
Section: Introductionmentioning
confidence: 99%